Nurses’ Challenges in Caring for Patients with COVID-19: A Qualitative Study - Mohammad Saeed Mirzaee; Akram Salamat; Marjan Mardani-Hamooleh; Zahra Abbasi; Tahmine Salehi (Journal of Qualitative Research in Health Sciences, 2022)
Background: Nurses who care for patients with coronavirus disease 2019 (COVID-19) face challenges in providing care for these patients. This study aimed to explain the nurses’ perception of challenges in caring for patients with COVID-19.Methods: This study was carried out using the content analysis method in 2020. In this study, 28 nurses were selected via purposive sampling. Individual and semi-structured interviews were conducted to collect the data. Data collection continued until data saturation. Content analysis was used to categorize the data and the method proposed by Elo and Kyngäs was also applied to analyze the data.Results: Nurses’ challenges were classified into three categories including organizational problems, defective communication process, and psychosocial challenges. The first category was divided into two subcategories including shortage of nurses and lack of personal protective equipment. The second category included two subcategories of defective communication with colleagues and defective communication with the patients and their families. Moreover, the third category was classified into two subcategories including psychological distress and sociocultural challenges.Conclusion: To address the challenges of nurses in caring for patients with COVID-19, the shortage of nurses should be eliminated. Nurses need to participate in comprehensive communication skills training courses. Furthermore, it is necessary to develop educational programs and present them to the public based on the cultural context of the society.